Childhood maltreatment and perceived stress in young adults: The role of emotion regulation strategies, self-efficacy, and resilience. (December 2018) - Hong, Fang; Tarullo, Amanda R.; Mercurio, Andrea E.; Liu, Siyu; Cai, Qiyue; Malley-Morrison, Kathleen
Abstract: Childhood maltreatment has many deleterious outcomes; however, trait resilience as well as emotion regulation strategies, including suppression and reappraisal, may mediate between childhood maltreatment and later perceived stress. For this study, 267 college students (183 females and 84 males; M age = 19.77, SD = 2.29) completed self-report measures of parental psychological and physical maltreatment, parental emotion neglect, habitual use of suppression and reappraisal strategies, emotion regulation self-efficacy, trait resilience, and recent perceived stress. Analyses were conducted to investigate gender-specific associations. In females, both suppression and reappraisal mediated the relationship between maternal/paternal emotional neglect and perceived stress, and suppression also mediated the relationship between maternal psychological maltreatment and perceived stress. Trait resilience mediated the relationships of all three types of maternal maltreatment, paternal psychological maltreatment, and paternal emotional neglect with perceived stress in females. There were no significant mediation effects in males. Thus, interventions aiming at reducing perceived stress associated with maternal or paternal emotional neglect or maternal psychological maltreatment in women may benefit from targeting both suppression and reappraisal. Such interventions may also be enhanced by efforts to strengthen trait resilience.